33-18=3(x-9)

Simple and best practice solution for 33-18=3(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33-18=3(x-9) equation:



33-18=3(x-9)
We move all terms to the left:
33-18-(3(x-9))=0
We add all the numbers together, and all the variables
-(3(x-9))+15=0
We calculate terms in parentheses: -(3(x-9)), so:
3(x-9)
We multiply parentheses
3x-27
Back to the equation:
-(3x-27)
We get rid of parentheses
-3x+27+15=0
We add all the numbers together, and all the variables
-3x+42=0
We move all terms containing x to the left, all other terms to the right
-3x=-42
x=-42/-3
x=+14

See similar equations:

| 9n^2–25=0 | | .04x+.07(100-x)=5 | | 21m+86=m+5 | | 114+(2y)=90 | | 9d-9=15d-1+4 | | -8-v=10+2v | | 2x-3=3x-47 | | 5x-4=-4x-31 | | 18.8+12.3n-16.9n=-0.3+14.5n | | -8s=-7s-7 | | 67-y=213 | | 500=1500/x | | x-18=x+54 | | -2(1+2x)=7–x | | 144+(2y)=90 | | a+3=a+2 | | -17m+m+20=-12m-20 | | 5n+7=7n+1= | | 275=-y+188 | | 4+3/5w=2 | | 154=-w+249 | | 0.25(2f-3)=0.05(10f-12) | | -16+3h=10-2h+19 | | 3x+7+113=180 | | 5t2-8t+10=0 | | 10+2c=-20 | | (v-5)(v+8)=0 | | 9+4=x;-5 | | h/9-18=-14 | | -19+19t=7t+14t+19 | | 8t+11t=35 | | 9-x=4;-5 |

Equations solver categories